Structural mimicry of the dengue virus envelope glycoprotein revealed by the crystallographic study of an idiotype–anti-idiotype Fab complex - Wong, Yee Hwa (2018)
A detailed understanding of the fine specificity of serotype-specific human antibodies is vital for the development and evaluation of new vaccines for pathogenic flaviviruses such as dengue virus (DENV) and Zika virus. In this study, we thoroughly characterize the structural footprint of an anti-idiotype antibody (E1) specific for a potent, fully human DENV serotype 1-specific antibody, termed HM14c10, derived from a recovered patient. The crystal structure at a resolution of 2.5 Å of a complex between the Fab fragments of E1 and HM14c10 provides the first detailed molecular comparison of an anti-idiotype paratope specific for a human antibody with its analogous epitope, a discontinuous quaternary structure located at the surface of the viral particle that spans adjacent envelope (E) proteins. This comparison reveals that the footprints left by E1 and E on HM14c10 largely overlap, explaining why the formation of binary complexes is mutually exclusive. Structural mimicry of the DENV E epitope by the E1 combining site is achieved via the formation of numerous interactions with heavy chain complementarity domain regions (CDRs) of HM14c10, while fewer interactions are observed with its light chain than for the E protein. We show that E1 can be utilized to detect HM14c10-like antibodies in sera from patients who recovered from DENV-1, infection suggesting that this is a public (common) idiotype. These data demonstrate the utility of employing an anti-idiotype antibody to monitor a patient's specific immune responses and suggest routes for the improvement of E “mimicry” by E1 by increasing its recognition of the Fab HM14c10 light chain CDRs.